2004
DOI: 10.1186/1471-2172-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in IgE- and Antigen-dependent histamine-release in peripheral blood of Schistosoma mansoni-infected Ugandan fishermen after treatment with praziquantel

Abstract: Background: Parasite-specific IgE levels correlate with human resistance to reinfection with Schistosoma spp. after chemotherapy. Although the role of eosinophils in schistosomiasis has been the focus of a great deal of important research, the involvement of other Fcε receptor-bearing cells, such as mast cells and basophils, has not been investigated in relation to human immunity to schistosomes. Chemotherapy with praziquantel (PZQ) kills schistosomes living in an in vivo blood environment rich in IgE, eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…For example, adult S. mansoni -antigen-induced HR from basophils passively sensitized with human infection sera increased post-treatment and suggested that IgG4-mediated down-regulation occurred during active infection [28]. We also observed increases in α-IgE-, SEA-, and SWA-HR in washed basophils from Ugandan fishermen exposed to S. mansoni [27], whereas Larson et al [33] reported increases in nonspecific IgE-dependent and IgE-independent HR in washed basophils following anthelmintic treatment of a small sample of Ascaris lumbricoides- and Trichuris trichiura -infected children.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, adult S. mansoni -antigen-induced HR from basophils passively sensitized with human infection sera increased post-treatment and suggested that IgG4-mediated down-regulation occurred during active infection [28]. We also observed increases in α-IgE-, SEA-, and SWA-HR in washed basophils from Ugandan fishermen exposed to S. mansoni [27], whereas Larson et al [33] reported increases in nonspecific IgE-dependent and IgE-independent HR in washed basophils following anthelmintic treatment of a small sample of Ascaris lumbricoides- and Trichuris trichiura -infected children.…”
Section: Discussionmentioning
confidence: 82%
“…HR assays followed a similar protocol to that described previously [ 27 ] but with the washing stage omitted, thus measuring direct HR by unwashed whole blood. Briefly, 25 µL of PIPES buffer was added to each well of glass fiber-coated microtitre antigen-coated plates to dissolve antigen, followed by 25 µL of unwashed whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies involve documentation of cases of schistosomiasis, their treatment and cure, and examinations at a later date to see if reinfections occurred [1],[2],[3],[4]. Of all the immunologic findings associated with these investigations, the most consistent observation is that resistance (usually defined as lower levels of infection) correlates with high IgE and low IgG4 antibodies against schistosome antigens [5],[6],[7],[8],[9],[10],[11],[12],[13],[14],[15],[16],[17],[18]. Other studies have reported that production of IFN-γ and IL-5 to schistosome antigens are also correlated with resistance [19],[20],[21],[22].…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind that schistosomiasis is a disease caused by intravascular worms, inhibition of active basophil degranulation may be necessary to prevent excessive allergic-like responses in the bloodstream. Interestingly, suppression of basophil function may be vital during PZQ treatment, which induces a massive allergic-like response upon the death of adult worms, with relatively few clinical symptoms (8, 62). …”
Section: 0 Discussionmentioning
confidence: 99%